Horseshoe Crabs of Western Part of Sarawak Coastal Waters: Distribution and Preliminary Molecular Study - Amni Nabilah, binti Mat Adam (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Horseshoe crabs are the oldest creature in the world and the concern for its status has increased. Present study was aimed to determine the distribution and preliminary genetic study of horseshoe crabs based on Cytochrome Oxidase I gene analysis at western part of Sarawak coastal waters. Field sampling was carried out during range of new moon days between October 2013 and March 2014 in Sibu Laut (01°41’18.2” N, 110°12’08.9”E) and Kg. Pasir Putih (01°39’49.0” N, 110°28’30.0”E). A total of 104 horseshoe crabs were collected throughout sampling sites (Sibu Laut=18; Kg. Pasir Putih=86) which two species present, Tachypleus gigas and Carcinoscorpius rotundicauda. There was relationship between body weight and carapace width of T. gigas at Sibu Laut and Kg. Pasir Putih. All physicochemical parameters was significant (p<0.05) in both sampling sites. Mean percentage of mass particle showed the particle size of sand was mostly medium sand (42.935± 21.800 %) at Sibu Laut whereas fine sand (53.514±8.495 %) at Kg. Pasir Putih. A total of 611bp COI gene sequence was obtained from T. gigas, SL1a2 and it matched with sequence of T. gigas, JF896114. Based on COI gene sequence analysis, T. gigas from Sibu Laut and other T.gigas from GenBank sample was monophyletic and formed a clade with high bootstrap value